A NEW RELATED SUBSTANCES METHOD DEVELOPMENT AND VALIDATION OF METRONIDAZOLE AND PREDNISOLONE BY USING EFFECTIVE LIQUID CHROMATOGRAPHIC METHOD - MANORANJANI, M.; ANITHA, D.; GAYATRI DEVI, NANDURI (International Journal of Applied Pharmaceutics, 2025)
Objective: The present study was aimed at developing and successively validating novel, simple, responsive and stable RP-UPLC (Reverse Phase Ultra Performance Liquid Chromatography) method for the estimation of active pharmaceutical ingredients of Metronidazole and Prednisolone and their related substances. Methods: The method of chromatography was fine-tuned with the use of the solution containing the contaminant. A phenyl column with dimensions of 50x2.1 mm and a particle size of 1.7 μm was used in the chromatographic procedure. The mobile phase consisted of acetonirile and 0.1 percent ortho-phosphoric acid (OPA) in a 50:50 v/v ratio, and isocratic elution was employed. The experimental parameters called for a PDA (Photo Diode Array) detector operating at 271 nm and a flow rate of 0.2 ml/min. Results: The resolution of Metronidazole, Prednisolone and their four related substances were greater than 2.0 for all pairs of components. The high correlation coefficient (R2>0.999) values indicated clear correlations between the investigated compound concentrations and their peak areas within the test ranges. The Repeatability and intermediate precision expressed by the Relative Standard Deviation (RSD) were less than 2. The accuracy evaluated by performing recovery studies via a spike method was 50-150%. The performance of the method was validated according to the present ICH (International Council for Harmonization) guidelines. Conclusion: We used the created technique to measure Metronidazole and Prednisolone with their associated contaminants and it was determined to be appropriate to routine analysis.